2016
DOI: 10.3201/eid2202.151516
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Fever with Renal Syndrome, Zibo City, China, 2006–2014

Abstract: Analysis of hemorrhagic fever with renal syndrome cases in Zibo City, China, during 2006–2014 showed that it occurred year-round. Peaks in spring and fall/winter were caused by Hantaan and Seoul viruses, respectively. Rodent hosts were the striped field mouse for Hantaan virus and the brown rat and house mouse for Seoul virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…With equal emphasis on rodent control and immunization, the incidence of HFRS was at a low level between 2007 and 2012. The incidence of HFRS increased slightly in 2013 and gradually decreased in later years, which was consistent with the epidemic trend for reported HFRS cases nationwide . This corresponds to characteristics of periodic epidemics for diseases with a natural infectious focus of infection.…”
Section: Discussionsupporting
confidence: 83%
“…With equal emphasis on rodent control and immunization, the incidence of HFRS was at a low level between 2007 and 2012. The incidence of HFRS increased slightly in 2013 and gradually decreased in later years, which was consistent with the epidemic trend for reported HFRS cases nationwide . This corresponds to characteristics of periodic epidemics for diseases with a natural infectious focus of infection.…”
Section: Discussionsupporting
confidence: 83%
“…Here, we found that the annual average incidence was 2.45/10 5 during 2007–2015, with a peak of 3.54/10 5 in 2012, while this incidence was 0.83/10 5 in China during 2006–2012. 9 HFRS peaks once a year in the fourth quarter in Qingdao but twice a year in Zibo (36°47′N118°3′E), 13 an inland city located at the northwest of Qingdao with a straight-line distance of 283 km. The dual peaks of HFRS each year in Zibo was proved to be associated with the existence of HTNV and SEOV.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in the rural population of two prefecture-level cities (Zibo and Qingdao) of China, we found HFRS had a high incidence rate which ranged from 1.96 cases/100,000 persons to 28.9/100,000 in different years [10,11]. These studies indicated HFRS was epidemic in these areas.…”
Section: Introductionmentioning
confidence: 79%
“…These studies indicated HFRS was epidemic in these areas. Peridomestic rodents were also captured for orthohantavirus detection in the two cities and orthohantavirus antigens were found by immunofluorescence assay in 5.2% (29/559) and 3.8% (9/240) of these rodents, respectively [10,11], and the seropositive rate to hantavirus of host animals was as high as 23.3% [12]. Hantaan orthohantavirus (HTNV) and Seoul orthohantavirus (SEOV) are the causative agents of HFRS in these areas.…”
Section: Introductionmentioning
confidence: 99%